Summary and policy implications - Badiane, Ousmane; Makombe, Tsitsi (International Food Policy Research Institute, 2015)
The 2014 Annual Trends and Outlook Report (ATOR) examines in depth the above developments and current and future trends that are likely to shape the course of African economies, as well as the key drivers of Africa’s recent growth recovery. The report also assesses the nature and pattern of Africa’s structural transformation process, past and future strategies for industrialization, changes occurring in agrifood systems, and the prospects for closing Africa’s significant infrastructure gap to boost future economic growth.